HUBUNGAN LAPORAN ONLINE DENGAN KEAKURATAN WAKTU PELAPORAN PROGRAM KIA OLEH KLINIK PRAKTEK BIDAN DI WILAYAH KERJA PUSKESMAS CIBEBER - Damai Yanti (Jurnal Kesehatan Rajawali, 2021)
According to the Republic of Indonesia Ministry of Health in 2013, routine recording and reporting starting from the puskesmas, district / city, province and central assessment results showed a delay of 51%. From the data obtained there are 6 health center in Cimahi City, one of which is the Cibeber health center with 13 Clinic of Midwife practice. Based on the results of interviews with all Clinic of in the Cibeber health center Work Area who reported on time as many as 8 Clinic of Midwife Practice (61.5%) and those who were not on time were 5 clinic of Midwife Practice (38.5%). Factors affecting late reporting of clinic of midewife Practice to puskesmas due to the workload of midwives and the collection of maternal and child health program reporting from Clinic of Midwife practice to health center require time efforts made to reduce delays in maternal and child health program reporting are made online by recording to facilitate midwife performance so as to minimize the occurrence of late reporting. The purpose of this study was to determine the relationship between online report and the timelines report of the maternal and child health program by clinic of Midwife practice in the Cibeber Health Center, Cimahi. The research method used is quasi-experimental research design with one group pre-test-post test design. The sample used in this study is total sampling. The variable measured in this study is the timeliness of reporting before and after using online report. The statistical test used is Chi Square research instruments using checklist. The results show that after using online records that reported on time were 12 clinic of Midwife practice (92.3%) and those who were not on time were 1 clinic of Midwife Practice (7.7%). The results of the analysis obtained p-value (0.03) <∝ (0.05), which means there is a relationship of timeliness before and after online report. Suggestions in this study to develop online records to be even better.